Digital media and depressive symptoms among Chinese adolescents: A cross-sectional study. Issue 5 (May 2019) - Zhang, Jie; Hu, Hang; Hennessy, Dwight; Zhao, Sibo; Zhang, Yiwen
Abstract: This study was designed to investigate the association between new digital media and depressive symptoms in a representative Chinese adolescent sample. An existing national data source was used, that surveyed 16, 205 Chinese adolescents in 2013–2014. Adolescents who spent more time on screen activities or less time on non-screen activities were significantly more likely to have depressive symptoms. New digital media had a greater association on girls than boys regarding depression. The association of new digital media on depression also showed a decreased trend across economic regions with the lower economically developed western area showing the greatest link between digital media and depression, although this association was still significant in all economic regions.